On the Performance Enhancement of Paging Systems Through Program Analysis and Transformations - Abu-Sufah; Kuck; Lawrie (IEEE transactions on computers, 1981)
It is possible to improve the paging performance of a program by applying transformations to the source program that improve data access locality. We discuss this subject in general terms, including automation of these transformations, and present a number of such transforms. This is followed by experimental results which indicate that these transformations are indeed effective. Use of practical, simple memory management policies like the fixed allocation local lru replacement algorithm leads to average improvements over untransformed programs of a factor of 10 in space-time cost, and a factor of 5 in memory size. Multiprogramming questions are also discussed.